The Effect of Adding Fennel Oil and Tartaric Acid on the Combustion Rate of CPKO Droplets - Putra Dwiantoko; Aulia Rahman; Slamet; Asri Anjasari; Novan Habiburahman (⁠International Journal of Sustainable Social Culture, Science Technology, Management, and Law Humanities, 2026)
This study examines the effect of combustion rate on CPKO (Crude Palm Kernel Oil) droplets with and without additives and catalysts, focusing on improving its combustion efficiency given that CPKO's primary component, palmitic acid (C16), inherently exhibits poor combustion characteristics. By incorporating fennel oil a bio-additive containing anethole with its conjugated cyclic structure capable of generating a magnetic field to weaken CPKO's molecular bonds and tartaric acid a highly electronegative catalyst that disrupts glycerol linkages the research demonstrates a significant enhancement in combustion rate, confirming the positive impact of these additives on CPKO's thermal decomposition.